2011
DOI: 10.1103/physrevlett.106.190601
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Matching Problem

Abstract: The matching problem plays a basic role in combinatorial optimization and in statistical mechanics. In its stochastic variants, optimization decisions have to be taken given only some probabilistic information about the instance. While the deterministic case can be solved in polynomial time, stochastic variants are worst-case intractable. We propose an efficient method to solve stochastic matching problems which combines some features of the survey propagation equations and of the cavity method. We test it on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…A pivotal role in this respect has been played by a paper by Liu et al [6], in which the problem of finding the minimal set of driver nodes necessary to control a network was mapped into a maximum matching problem. Using a well established statistical mechanics approach [22][23][24][25][26][27], Liu et al [6] characterize in detail the set of driver nodes for real networks and for ensembles of networks with given in-degree and out-degree distribution. By analyzing scale-free networks with minimum in-degree and minimum out-degree equal to 1 they have found that the smaller is the power-law exponent γ of the degree distribution, the larger is the fraction of driver nodes in the network.…”
mentioning
confidence: 99%
“…A pivotal role in this respect has been played by a paper by Liu et al [6], in which the problem of finding the minimal set of driver nodes necessary to control a network was mapped into a maximum matching problem. Using a well established statistical mechanics approach [22][23][24][25][26][27], Liu et al [6] characterize in detail the set of driver nodes for real networks and for ensembles of networks with given in-degree and out-degree distribution. By analyzing scale-free networks with minimum in-degree and minimum out-degree equal to 1 they have found that the smaller is the power-law exponent γ of the degree distribution, the larger is the fraction of driver nodes in the network.…”
mentioning
confidence: 99%
“…This is known to be an NP-Hard problem, as proved in [18]. Several approximation factors to this problem are also proposed [2,9].…”
Section: Stochastic Constraint Programming and Related Workmentioning
confidence: 99%
“…To take into account this uncertainty, we shall work with an objective function which is averaged over the possible outcomes of the observation. More precisely, the above diagnosis problem is a multistage stochastic optimization problem, a subject that has been extensively studied in the optimization community [34,[49][50][51].…”
Section: Problem Statementmentioning
confidence: 99%
“…Our approach is of course computationally more expensive than the previous approaches, but it shows how different types of interactions could be helpful in the course of diagnosis. Additionally, because of recent developments in related fields [32][33][34][35], we now have the necessary concepts and tools to address difficulties in more sophisticated (realistic) problems of this type. This study does not involve usage of real medical data, which is by the way fundamentally incomplete at this moment for such modeling; however, it provides a rationale as to why certain often-neglected statistical information and medical data can be useful in diagnosis and demonstrates that investments in collecting such data will likely pay off.…”
Section: Introductionmentioning
confidence: 99%